2012
DOI: 10.1891/1946-6560.3.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Violent Couples Seeking Therapy: Bilateral and Unilateral Violence

Abstract: Little information is available about couples experiencing intimate partner violence (IPV) who voluntarily seek couples therapy. We examined the characteristics of 129 couples who sought therapy for IPV to learn more about this population. A majority of the sample, 74%, experienced bilateral physical violence, 16% experienced unilateral male violence, and 5% experienced unilateral female violence. Conflict theory is used to explain the finding that couples experiencing bilateral violence reported higher levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Stith and colleagues (Stith et al, 2011;Madsen, Stith, Thomsen, & McCollum, 2012) suggested that not all violence is the same, and that society now conceptualizes IPV more from a scientific perspective than a political one. They suggested that this is one of the most important breakthroughs on understanding of IPV given the growing body of research indicating heterogeneity among couples experiencing IPV.…”
Section: Typologies Of Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Stith and colleagues (Stith et al, 2011;Madsen, Stith, Thomsen, & McCollum, 2012) suggested that not all violence is the same, and that society now conceptualizes IPV more from a scientific perspective than a political one. They suggested that this is one of the most important breakthroughs on understanding of IPV given the growing body of research indicating heterogeneity among couples experiencing IPV.…”
Section: Typologies Of Violencementioning
confidence: 99%
“…Various forms of IPV, including those that do not result in physical injuries, have negative impacts on relationships (Andrews, Foster, Capaldi, & Hops, 2000;Bradbury & Lawrence 1999;Madsen et al, 2012;Panuzio & DiLillo, 2010;Shortt, Capaldi, Kim, & Laurent, 2010). Even though there is research to support that both males and females are victims of IPV (Archer, 2000;, the consequences of maleperpetrated violence are more destructive to female victims than female-perpetrated IPV towards males (Ackerman, 2012;Stith, et al, 2008).…”
Section: Relational Satisfaction and Ipvmentioning
confidence: 99%
“…The qualitative research approach used here has the potential to provide more information on the role of dyadic interactions in the production of violence, and thus to provide a better understanding of the context of violence-a need that has been identified by several authors (Madsen, Stith, Thomsen, & McCollum, 2012;Whitaker et al, 2007;Yoon & Lawrence, 2013). With these aims in view, the analytical method used in our study was Dialogical Investigations of Happenings of Change (DIHC; Seikkula et al, 2012), which was the first research method to focus on multi-actor dialogue settings.…”
mentioning
confidence: 99%
“…2 We consider both aspects to be crucial since very little research has been conducted in the field of IPV under these conditions, even if the relevance of these aspects has been repeatedly demonstrated (Madsen et al, 2012;Stith et al, 2012).…”
mentioning
confidence: 99%
“…Furthermore, in couples with bilateral violence, where both partners assault each other, a traditional male batterer program may not be enough intervention to stop violence in the relationship. A recent study of couples seeking treatment for IPV (n 5 129 couples) found that most of the sample, 74%, experienced bilateral physical violence (Madsen, Stith, Thomsen, & McCollum, 2012). Cessation of partner violence by one partner is highly dependent on whether the other partner also stops the violence (Feld & Straus, 1989).…”
mentioning
confidence: 99%